2020
DOI: 10.1371/journal.pone.0227472
|View full text |Cite
|
Sign up to set email alerts
|

Association between tuberculosis and depression on negative outcomes of tuberculosis treatment: A systematic review and meta-analysis

Abstract: Background Depression is a common comorbidity of tuberculosis (TB) and is associated with poor adherence to treatment of multiple disorders. We conducted a systematic review to synthesize the existing evidence on the relationship between depression and negative outcomes of TB treatment. Methods We systematically reviewed studies that evaluated depressive symptoms (DS) directly or indirectly through psychological distress (PD) and measured negative treatment outcomes of drug-sensitive pulmonary TB, defined as d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 33 publications
3
62
0
1
Order By: Relevance
“…This may be due to the small sample of patients. This study showed an association of depression with less effective TB therapy, which is also reflected in a systematic review and meta-analysis in 2020 [24].…”
Section: Discussionsupporting
confidence: 70%
“…This may be due to the small sample of patients. This study showed an association of depression with less effective TB therapy, which is also reflected in a systematic review and meta-analysis in 2020 [24].…”
Section: Discussionsupporting
confidence: 70%
“…Although we did not formally measure depression, more than one fifth of patients who reported missing doses described feeling depressed as a reason. In a recent systematic review, researchers found that depression is associated with increased loss to follow up and death—but not medication nonadherence—during TB treatment; however, the studies that were included had suboptimal measures of adherence [ 41 ]. Future studies using rigorous measures of both depression and adherence, such as the urine testing we used here, may clarify whether nonadherence mediates the association between depression and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The syndemics of HIV and tuberculosis and HIV and depression are well-recognized (10), but that of tuberculosis and depression lags behind both. Up to 70% of tuberculosis patients may present with depression (11,12), associated with poor healthcare seeking behavior and disengagement from treatment, leading to poorer outcomes, including loss to follow-up and death (13). Tuberculosis and depression share common risk factors, including homelessness, HIV co-infection, and alcohol and substance dependency (13): depression thus increases the risk for acquiring tuberculosis.…”
Section: The Interaction Between Tuberculosis and Depressionmentioning
confidence: 99%